1975
DOI: 10.1128/aac.7.3.294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rifampin on Nasal Carriage of Staphylococcus aureus

Abstract: Initial studies indicate that rifampin may be useful for the treatment of Staphylococcus aureus infections. Because bacterial resistance to rifampin may develop rapidly, its widespread use could result in the emergence of a resistant flora. This study evaluates the effectiveness of rifampin in reducing the nasal carriage of S. aureus and the rate at which resistant mutants emerge in a tuberculosis hospital where the drug was widely used. Anterior nares cultures were performed four times over a 13-month period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
1

Year Published

1978
1978
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(18 citation statements)
references
References 10 publications
1
16
0
1
Order By: Relevance
“…Such cases, exemplified by rifampicin treatment of Escherichia coli, may reflect our inability to achieve drug concentrations that are high enough to block mutant growth (single-step mutants are highly protective). A wide selection window explains why rifampicin, a very active agent with S. aureus, is often unsuitable for monotherapy with this pathogen [21,22].…”
Section: Measuring the Mutant Selection Windowmentioning
confidence: 99%
“…Such cases, exemplified by rifampicin treatment of Escherichia coli, may reflect our inability to achieve drug concentrations that are high enough to block mutant growth (single-step mutants are highly protective). A wide selection window explains why rifampicin, a very active agent with S. aureus, is often unsuitable for monotherapy with this pathogen [21,22].…”
Section: Measuring the Mutant Selection Windowmentioning
confidence: 99%
“…Rifampin has a high degree of activity against MRSA; however, the development of resistance is a well-recognized problem when rifampin is used alone (6,42,51,56). When T/S plus rifampin is used in combination, the level of resistance to rifampin is reduced.…”
mentioning
confidence: 99%
“…Nevertheless, the only references on the subject are by Spink et al (32), who in 1951 reported the absence of resistance in eight patients with brucellosis and bacteremia persisting after 10 to 14 days of treatment with sulfamide and streptomycin; Hall and Spink (15) also mention a patient who developed streptomycin resistance during treatment with the drug. The question of the development of resistance is of particular interest for patients relapsing after rifampin treatment with regard to the emergence of rifampin-resistant Brucella variants observed in in vitro studies (8) and reported for the same drug in other types of infections (4,27,33).…”
mentioning
confidence: 99%